O uso da informação do ambiente organizacional por indústrias do setor metal-mecânico de micro e pequenos portes da região de Passo Fundo - RS - Marilaine Schaun Pelufe (2005)
The objective of this study was to identify the relative importance of different sources of information for decision support in the steel-metallurgy business sector. The survey was carried out in small scale businesses located at the Passo Fundo county, Rio Grande do Sul State, Brazil. This study arises from the analysis of the competitive intelligence and their basic processes in order to investigate the sourcesof information used by the managers. Each source of information was analyzed regarding frequency of utilization, relevance and reliability. The results show that the customers sector is the one with the highest level of importance in relation to trends and events. The survey reveals that the traditional media types are the most frequently used while, regarding relevance and reliability, the customers are sources most frequently mentioned.